How do you solve \frac { b } { b + 7} - 9= \frac { - 7} { b + 7}bb+79=7b+7?

1 Answer
May 25, 2017

No solution

Explanation:

Multiply both sides by b+7b+7. Note that this means that b!=-7b7:

(b+7)(b/(b+7)-9)=(b+7)(-7/(b+7))(b+7)(bb+79)=(b+7)(7b+7)

This becomes:

b-9b-63=-7b9b63=7

Consolidate the bbs:

-8b-63=-78b63=7

Add 6363 to both sides:

-8b-63+63=-7+638b63+63=7+63

This becomes:

-8b=568b=56

Divide both sides by -88:

(-8b)/-8=56/-88b8=568

This becomes:

b=-7b=7

However, don't forget about the initial condition. bb is not allowed to be -77. So we have no solution.